2021
DOI: 10.1007/s00784-021-04208-9
|View full text |Cite
|
Sign up to set email alerts
|

The association between coffee consumption and periodontitis: a cross-sectional study of a northern German population

Abstract: Background Positive and negative influences on oral health are attributed to coffee consumption. The aim of the current study is to evaluate the association between coffee consumption and periodontitis in the general population of Hamburg. Methods A total of 6,209 participants from the Hamburg City Health Study were included in this cross-sectional study. Information on coffee consumption was collected using a food frequency questionnaire. Periodontal exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…The oral cavity is the first organ of the body to come in contact with coffee, and residual coffee components in the oral cavity after drinking may affect the health of periodontal tissues. Most studies have confirmed the benefits of coffee consumption in periodontal health [ 23 , 35 , 36 , 37 , 38 ]. In addition, CGA in coffee has a direct inhibitory effect on P. gingivalis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oral cavity is the first organ of the body to come in contact with coffee, and residual coffee components in the oral cavity after drinking may affect the health of periodontal tissues. Most studies have confirmed the benefits of coffee consumption in periodontal health [ 23 , 35 , 36 , 37 , 38 ]. In addition, CGA in coffee has a direct inhibitory effect on P. gingivalis [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CGA in coffee has a direct inhibitory effect on P. gingivalis [ 39 ]. However, a cross-sectional survey in Germany showed that moderate (3–6 cups/day) coffee consumption was not associated with periodontitis, whereas heavy coffee consumption (>7 cups/day) was significantly associated with periodontitis [ 35 ]. Studies on the effects of coffee and its main constituents, CA and CGA, on periodontitis are limited, and the results are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…One study used data from dental longitudinal studies, one study used data from Genome and Epidemiology Study, one used general population, and one other study selected chronic periodontitis patients who had received initial treatment as the participants of the study. All of the human studies used questionnaire to assess the dose of daily coffee consumption (all six studies), [8][9][10][11][12][13] one study also used Cornell Medical Index (CMI) to gain coffee consumption in addition to questionnaire. 9 Two studies admitted that validity and reliability test of the questionnaire were not performed sufficiently, therefore, further research is required.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…11 The clinical oral examination performed to assess periodontal health including scoring method according to American Association of Periodontology by probing pocket depth and clinical attachment level, 12 using Community Periodontal Index (CPI), 8,10 radiographic examination to measure alveolar bone loss, measurement of probing depth, 9,13 bleeding on probing, 9,13 gingival recession, 13 and examining supragingival calculus, 9,13 and plaque index score. 13 Aside from periodontal health, caries measurement using DMFT index was also performed. 13 In terms of bias, some studies also observed several confounding factors, such as Body Mass Index (BMI) 9,11,13 and other nutritional intake, 11 smoking and alcohol habit, 9,[11][12][13] medical history such as diabetes, 8,9,12,13 cholesterol level 8 and coronary heart diseases, 12,13 blood sample analysis, 8 and other socio-demographic factors.…”
Section: Methodological Qualitymentioning
confidence: 99%
See 1 more Smart Citation